Advancing E-Learning Adoption in Saudi Arabia: Extending TAM with Multi-Level External Variables and Accessibility - Alsubaie, Raghad; Shariff, Sya Azmeela; Ismail, Syuhaida; Masrom, Maslin (Advances in Social Sciences Research Journal, 2025)
This study explores the key factors influencing the adoption of E-learning systems among undergraduate students in Saudi Arabia by extending the Technology Acceptance Model (TAM) with multi-level external variables. These include individual-level factors (self-efficacy, enjoyment, computer anxiety), cultural-level (subjective norms, experience), and system-level (content quality). Furthermore, the study examines the moderating effect of accessibility on the relationships between perceived usefulness, perceived ease of use, and intention to use Blackboard as a representative E-learning platform. Data collected from 400 undergraduate students at Shaqra University and analyzed using PLS-SEM. The findings indicated that self-efficacy significantly predicts perceived ease of use but not perceived usefulness. Subjective norms positively influenced only perceived usefulness. Enjoyment and experience positively affected both perceived ease of use and usefulness, while computer anxiety negatively impacts ease of use alone. Content quality demonstrates a strong positive effect on both core TAM constructs. Accessibility moderates the relationship between ease of use and intention to use Blackboard. Aligned with Saudi Vision 2030’s educational goals, these findings highlight the importance of digital infrastructure, skill development, and inclusive access in shaping students’ adoption of E-learning technologies.